The Relationship Between Educators' Attention With Discipline of Students at TPQ/TQA Masjid Al-Muhajirin Pasir Putih Tabing Padang City - Azmi, Nurul; Ismaniar, Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by the poor discipline of students at the TPQ/TQA Al-Muhajirin PasirPutih Tabing Mosque, Padang City. This is thought to be due to poor attention from educators,resulting in poor student discipline at the TPQ/TQA Al-Muhajirin Mosque. The purpose of thisresearch is to: 1) See a picture of educators' attention in disciplining students at the TPQ/TQA AlMuhajirin Pasir Putih Tabing Mosque, Padang City. 2) See the picture of student discipline at theTPQ/TQA Al-Muhajirin Pasir Putih Tabing Mosque, Padang City. 3) Seeing the relationship betweeneducators' attention and student discipline at the TPQ/TQA Al-Muhajirin Pasir Putih TabingMosque, Padang City. This research uses a quantitative approach with a correlational type of research.The population in this study was 60 people and the sample taken was 30 people or 50% with samplingusing a stratified random sampling technique. The questionnaire was used as a data collection tool,and data analysis used percentage and product moment formulas.The results of the research showthat: 1) The description of educators' attention at the TPQ/TQA Al-Muhajirin Pasir Putih TabingMosque, Padang City, is categorized as poor; 2) The description of student discipline at theTPQ/TQA Al-Muhajirin Pasir Putih Tabing Mosque, Padang City, is categorized as poor; 3) There isa significant relationship between educators' attention and student discipline at the TPQ/TQA AlMuhajirin Pasir Putih Tabing Mosque, Padang City. The research suggestions are: 1) It is hoped thateducators can increase attention to students so that they can foster a high sense of discipline instudents; 2) It is hoped that students can instill a disciplined attitude in learning so that students canachieve maximum learning results; 3) It is hoped that future researchers will be able to innovate inresearching new variables so that they can increase and complete the variables in research.Keywords: Educator Attention, Student Discipline